151 quick ideas to improve your people skills - Dittmer, Robert E., 1950-; McFarland, Stephanie, 1968- (151 quick ideas., 2018)
151 Quick Ideas to Improve Your People Skills is constructed to help everyone do a better, more effective job of working with others.